Low interest rates and the distribution of household debt - Marina Emiris; François Koulischer (National Bank of Belgium, 2021)
We study how changes in interest rates affect the borrowing of households and the distribution of debt within the population. In a model of household borrowing with credit constraints and endogenous house prices, we show that less constrained households with more pre-existing housing wealth increase their borrowing most when interest rates fall. We then use unique loan level data on the universe of household credit in Belgium to document a shift in the distribution of debt over age, with older households borrowing more as interest rates fell in the last decade. First-time borrowers, who are more likely to be constrained, do not contribute to the rise in household debt. To identify the elasticity of household debt to the interest rate, we use regulatory data on foreign exposures of banks and on the location of bank branches. We find that a 1 percentage point fall in the interest rate is associated with a 15% growth in household debt.
Keywords: D14; E43; E58; G51; 330; Interest Rates; Household Debt; Mortgages; Credit Constraints